Social and economic impacts of the donkey skin trade on donkey-dependent women and communities in Kenya - David Obiero Oduori; Gilbert Kirui; Robert Ofwete; Ronald K. Sang; Christine Were; Laura M. Kubasiewicz (Human-Animal Interactions)
Abstract Women in sub-Saharan Africa experience considerable economic vulnerability, with many living on less than US$1.90 per day. These women rely heavily on donkeys to perform essential daily tasks, enabling them to balance family and livelihood responsibilities. However, the rapid expansion of the donkey skin trade, driven by the demand for the Chinese product ejiao, has increased the incidence of donkey theft and illegal slaughter. Although a recent ban on the donkey skin trade across Africa offers some hope, a thorough understanding of the impact of this trade is critical for the development of informed policy and support for vulnerable women. Through questionnaires and key informant interviews, we explore the relationship between women and their donkeys, and examine the repercussions of donkey loss on women, families, and communities dependent on donkeys for stability and income. We highlight the steps these women have taken to protect their donkeys from theft and outline direct awareness and impacts of the skin trade on women’s lives and livelihoods. While impacts varied between locations, women in donkey-reliant communities can be significantly affected, with those in one of the studied communities forfeiting up to 73% of their household income following the loss of donkeys. The impact of the trade extended beyond financial loss, manifesting as emotional strain, health issues, and disruption of children’s education. Replacing lost donkeys often involved trade-offs such as delaying school fees, scaling back investments, and limiting access to basic necessities. Rising purchase costs for donkeys made replacement challenging, perpetuating these impacts. Findings also revealed that local efforts to protect donkeys may be insufficient without external support from both non-government-organization interventions and enforcement of government-led policy change. We strongly advocate for the continuation of Kenya’s moratorium on the trade and emphasize the need for policies and programs focused on enhancing donkey welfare and supporting donkey-dependent communities.